2020
DOI: 10.1007/978-3-030-49916-7_105
|View full text |Cite
|
Sign up to set email alerts
|

Design and Fabrication of a Non-standard, Structural Concrete Column Using Eggshell: Ultra-Thin, 3D Printed Formwork

Abstract: This paper describes the design and fabrication process of a concrete column cast in ultra-thin, 3D printed formwork, using a process known as Eggshell. The column was prefabricated as part of a real-world construction project, serving as the main load-bearing element for a reciprocal timber frame structure. The fabrication of the column required upscaling of the Eggshell process, to allow for the fabrication of elements of an architectural scale. Furthermore, several challenges had to be addressed such as: in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…The concept of simultaneous formwork fabrication and concrete casting pushes this idea a step further and can prove to be a powerful tool in on-site construction. 80 Depending on what happens to the formwork once the concrete cures, two main categories can be defined: remov-able and stay-in-place. Five further subtypes are discussed in Table 2 in relation to a series of example projects and the concreting method.…”
Section: Classification Of 3d Printed Formwork Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The concept of simultaneous formwork fabrication and concrete casting pushes this idea a step further and can prove to be a powerful tool in on-site construction. 80 Depending on what happens to the formwork once the concrete cures, two main categories can be defined: remov-able and stay-in-place. Five further subtypes are discussed in Table 2 in relation to a series of example projects and the concreting method.…”
Section: Classification Of 3d Printed Formwork Strategiesmentioning
confidence: 99%
“…The concept of simultaneous formwork fabrication and concrete casting pushes this idea a step further and can prove to be a powerful tool in on-site construction. 80 …”
Section: Classification Of 3d Printed Formwork Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactor presented in this study is built upon a previous system used for the robotic slip forming of façade mullions installed in the DFAB HOUSE, Empa Dübendorf (Switzerland) [ 14 , 15 ] as well as for casting in the 3D-printed Eggshell formwork with variable cross section, further described in [ 14 ]. The system relies on a retarded mix, which was pumped in sequential batches (discontinuously) into a mixer placed above a formwork, in which an accelerator was added.…”
Section: Background and Requirementsmentioning
confidence: 99%
“…However, breakage occurred in the 45°m odel after filling to 100 mm in height. 34 A later study showed that it was also possible to print and fill volumes of a smaller diameter with an overhang of 65°by changing the printing speed based on the angle between layers. 35 In case of a larger overhang, one can print more slowly while keeping the flow rate constant to deposit more material in one place and create a stronger bond between layers.…”
Section: Process Developmentmentioning
confidence: 99%